2022
DOI: 10.3390/su141912068
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Distribution Characteristics and Influencing Factors of Hakka Traditional Villages in Fujian, Guangdong, and Jiangxi, China

Abstract: Hakka traditional villages are an important segment of traditional Chinese villages. Analysis of the process of selection of a Hakka site can deepen our knowledge of Hakka culture. In this study, we selected Hakka traditional villages in Fujian, Guangdong, and Jiangxi provinces as research sites. We extracted basic data for these traditional villages using geographic information system coordinates, identified several potential influencing factors, and analyzed correlations among the factors using the R languag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…The effects of population and transportation are similar to other studies by Chen 42 , Li 12 , Xie 54 and others. However, it should be noticed that the poor accessibility of traditional villages also maps the psychology of the ancient Jiarong Tibetans in pursuit of residential security.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The effects of population and transportation are similar to other studies by Chen 42 , Li 12 , Xie 54 and others. However, it should be noticed that the poor accessibility of traditional villages also maps the psychology of the ancient Jiarong Tibetans in pursuit of residential security.…”
Section: Discussionsupporting
confidence: 89%
“…Meanwhile, with digital technologies such as ArcGIS and CIM becoming more and more mature, the exploration about the driving mechanism of spatial distribution is getting deeper. Based on ArcGIS, Geodetector, Multi-scale Geography Weighted Regression (MGWR) to carry out the study of spatial differentiation 15 , 53 , 54 , geographic pattern 44 , 51 , and spatio-temporal evolution 46 , 55 , 56 of traditional villages, which facilitates the identification with the core influences. These are currently effective means for quantitatively analyzing the distributional characteristics and formation of traditional villages.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nineteen GIAHSs in China are collected from FAO, 1 114 AHSs and 399 PAHSs are collected from the Ministry of Agriculture of China. 2 Previous studies have found that cultural heritage distribution was affected by many factors, such as natural factors, society, economy, and culture (Jin et al, 2022;Nie et al, 2022;Xie et al, 2022). We collect the potential influencing factors and classified them into two dimensions, namely, natural factors (i.e., annual average temperature, annual average precipitation, elevation, soil, and river) and human factors (i.e., economy, population, and culture), and explore the pattern and rule of CAHSs distribution.…”
Section: Data Sourcesmentioning
confidence: 99%
“…This technique has been widely used to analyze the correlation between various cultural heritages and physical, cultural, and socio-economic factors, such as archaeological sites (Yagoub, and Al yammahi, A. A., 2022), historic villages (Jin et al, 2022;Xie et al, 2022), industrial heritage (Zhang et al, 2022), and intangible heritage (Nie et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Scholars have studied traditional villages in terms of their spatial characteristics, cultural landscape, value assessment, conservation, and tourism development, building a relatively comprehensive knowledge system of cultural heritage regarding traditional villages [4][5][6][7][8][9][10]. Furthermore, scholars have studied the spatial distribution of traditional villages in Hunan using kernel density analysis, the nearest neighbor index, and spatial autocorrelation analysis [11][12][13][14]. However, few researchers have studied the historical stages of the development of traditional villages in Hunan, and little is known about the historical background reflected by the evolutionary pattern and changes in traditional villages.…”
Section: Introductionmentioning
confidence: 99%